2017
DOI: 10.18632/oncotarget.21009
|View full text |Cite
|
Sign up to set email alerts
|

Large granular lymphocytosis after transplantation

Abstract: Post-transplant lymphoproliferative disorders (PTLD) represent a heterogeneous group of diseases that occur following transplantation. Large granular lymphocytic (LGL) lymphocytosis is one type of PTLD, ranging from reactive polyclonal selflimited expansion to oligo/monoclonal lymphocytosis or even to overt leukaemia.LGL lymphocytosis in transplant recipients may present as a relatively indolent version of the condition and may be more common than reported, but its natural history and clinical course have not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 69 publications
1
2
0
Order By: Relevance
“…In our samples, these motifs of HLA-A*0201, CMV + CDR3s were more represented in expanded clones of CMV + subjects than in CMV − cases (Fisher test; P = 0.033). These results added to validity of our current analysis and to a hypothesis that chronic CMV antigen stimulation is a potential driver of T cell clonal expansion 33 .…”
Section: Resultssupporting
confidence: 64%
“…In our samples, these motifs of HLA-A*0201, CMV + CDR3s were more represented in expanded clones of CMV + subjects than in CMV − cases (Fisher test; P = 0.033). These results added to validity of our current analysis and to a hypothesis that chronic CMV antigen stimulation is a potential driver of T cell clonal expansion 33 .…”
Section: Resultssupporting
confidence: 64%
“…Several mechanisms of clonal expansion post‐transplantation may be responsible, including active viral infections, latent oncogenic viral reactivation, graft allo‐antigenic stimulation or reactivation of a pre‐existing autoimmune process (Fig ). In general, although oligoclonal skewing has been described after transplantation (Gorochov et al , ; Mohty et al , ; Sabnani et al , ; Qiu et al , ), the vast majority of patients with this complication is not known to develop T‐LGLL. Theoretically, T‐LGLL may originate from pre transplantation autoimmunity of the donor in HSCT or recipient in SOT, which has been augmented by a heightened level of immune responsiveness due to allo‐stimulation.…”
Section: Type Of Transplantation and Individual Characteristics Of Pomentioning
confidence: 99%
“…It has been observed that LGL is often associated with chronic CMV infection as well as patients with chronic GvHD through a process of chronic antigenic stimulation. LGL is a phenomenon estimated to affect between 0.5% and 18.4% of patients following HSCT 11 . The presentations can range from self-limiting polyclonal expansion to overt leukemia.…”
Section: Discussionmentioning
confidence: 99%